Mechanisms of lipid droplet biogenesis. Issue 13 (9th July 2019) - Chapman, Kent D.; Aziz, Mina; Dyer, John M.; Mullen, Robert T.
Abstract : Lipid droplets (LDs) are organelles that compartmentalize nonbilayer-forming lipids in the aqueous cytoplasm of cells. They are ubiquitous in most organisms, including in animals, protists, plants and microorganisms. In eukaryotes, LDs are believed to be derived by a budding and scission process from the surface of the endoplasmic reticulum, and this occurs concomitantly with the accumulation of neutral lipids, most often triacylglycerols and steryl esters. Overall, the mechanisms underlying LD biogenesis are difficult to generalize, in part because of the involvement of different sets of both evolutionarily conserved and organism-specific LD-packaging proteins. Here, we briefly compare and contrast these proteins and the allied processes responsible for LD biogenesis in cells of animals, yeasts and plants.